Glycerol Monolaurate to Ameliorate Efficacy of Inactivated Pseudorabies Vaccine - Ren, Qinghai; Wang, Xiaobo; Gao, Qingqing; Wang, Gaiqin; Chen, Xiaochen; Liu, Chunxue; Gao, Song; Li, Yubao (Frontiers in Veterinary Science, 2022)
The present study aimed to evaluate the effect of glycerol monolaurate (GML) on the growth performance and immune enhancement of pseudorabies virus (PRV) inactivated vaccine in the early-weaned piglets. One hundred and twenty-five 28-day-old weaned piglets were randomly assigned to a control group (CON, no vaccine and no challenge), challenge control group (C-CON), inactivated PRV vaccine group (IPV), IPV + 500 mg/kg GML group (L-GML), and IPV + 1000 mg/kg GML group (H-GML) during the entire 28-day experimental period. All the data analysis were performed by one-way analysis of variance and multiple comparison. Our results showed that the final weight, average daily gain (ADG) and average daily feed intake (ADFI) of H-GML was the highest in each group, and F/G of H-GML were increased but there was no significant difference with CON (p＞0.05). Levels of PRV gB antibody and immunoglobulin in serum of L-GML and H-GML were higher than those of IPV, but only gB antibody levels and immunoglobulin G (IgG) in H-GML significantly increased (p＜0.05). Compared with IPV, the contents of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1β (IL-1β) in serum of L-GML (TNF-α and IL-1β: p＞0.05, IL-6: p＜0.05, respectively) and H-GML (p＜0.01, both) were all decreased, and the content of interleukin-10 (IL-10) in H-GML was increased (p＞0.05). Furthermore, reverse transcription-polymerase chain reaction (RT-PCR) experiments proved that L-GML and H-GML were both superior to IPV in inhibiting the expression of TNF-α (p＜0.01), IL-6 (p＞0.05) and IL-1β (p＜0.01) mRNAs, and promoting the expression of IL-10 mRNA (L-GML: p＞0.05, H-GML: p＜0.05, respectively) in the superficial inguinal lymph nodes. Histopathological examination found that mild congestion in the lung and inguinal lymph nodes of IPV, while the tissues (brain, lung and inguinal lymph nodes) of L-GML and H-GML were the same as CON with no obvious lesions. The above results indicate that GML may improve growth performance of weaned piglets and enhance the immunity of PRV inactivated vaccine by increasing the levels of PRV gB antibody and immunoglobulin, and regulating cytokine levels.